Absence of a Runaway Greenhouse Limit on Lava Planets - Iris D. Boer; Harrison Nicholls; Tim Lichtenberg (The Astrophysical Journal)
Climate transitions on exoplanets offer valuable insights into the atmospheric processes governing planetary habitability. Previous pure-steam atmospheric models show a thermal limit in outgoing long-wave radiation, which has been used to define the inner edge of the classical habitable zone and guide exoplanet surveys aiming to identify and characterize potentially habitable worlds. We expand upon previous modelling by treating (i) the dissolution of volatiles into a magma ocean underneath the atmosphere, (ii) a broader volatile range of the atmospheric composition including H _2 O, CO _2 , CO, H _2 , CH _4 , and N _2 , and (iii) a surface-temperature- and mantle-redox-dependent equilibrium chemistry. We find that multicomponent atmospheres of outgassed composition located above partially or fully molten mantles do not exhibit the characteristic thermal radiation limit that arises from pure-steam models, thereby undermining the canonical concept of a runaway greenhouse limit, and hence challenging the conventional approach of using it to define an irradiation-based habitable zone. Our results show that atmospheric heat loss to space is strongly dependent on the oxidation and melting state of the underlying planetary mantle, through their significant influence on the atmosphere’s equilibrium composition. This suggests an evolutionary hysteresis in climate scenarios: Initially molten and cooling planets do not converge to the same climate regime as solidified planets that heat up by external irradiation. Steady-state models cannot recover evolutionary climate transitions, which instead require self-consistent models of the temporal evolution of the coupled feedback processes between interior and atmosphere over geologic time.